Inlay butterfly cartilage tympanoplasty for large central perforations - Karatas, Mehmet; Dogan, Sedat (The European Research Journal, 2017)
Objective. The aim of this study is to evaluate the results of inlay butterfly tympanoplasty technique in large central tympanic membrane perforations. Methods. The files of the patients who underwent inlay butterfly cartilage tympanoplasty for large central tympanic membrane perforations were reviewed. Patients were followed with otoscopy and audiometry. Preoperative and postoperative pure-tone audiometry results were calculated and analyzed to evaluate the hearing gain. The grafting procedure was considered successful if no perforations were observed during postoperative microscopic or endoscopic evaluation during the follow-up period. Results. Twenty-nine patients with large central tympanic membrane perforation who were operated by inlay butterfly tympanoplasty technique were included in the study. Twenty-one (72.4%) ears were operated with endoscope and 8 (27.6%) under microscope. The mean duration of surgery was 30.5±3.77 minutes. The mean follow-up time was 69.6±21.6 (range; 24-112 weeks). Graft take rate was 89.7% (26/29). Conclusion. Inlay butterfly cartilage tympanoplasty is a minimal invasive and effective technique for repairing large central tympanic membrane perforations.